Kewajiban Calon Notaris Untuk Merahasiakan Segala Sesuatu Mengenai Akta Yang Dibuatnya Dan Segala Keterangan Yang Diperoleh Guna Pembuatan Akta (Analisis Yuridis Pasal 16A Ayat (2) Undang-Undang Republik Indonesia Nomor 2 Tahun 2014 Tentang Perubahan Atas - Ardhina Noor Malida (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2015)
Abstract There is a chapter on the addition of a notary candidate apprenticeship in UUJN No. 2 in 2014, namely Article 16A paragraph (2) which regulates the obligations of the notary internship. The article above sounds vague and contrary to Article 1 paragraph (1) and Article 15 paragraph (1) UUJN authority of a notary. This research has the goal to determine the ratio legis provisions of Article 16A (2) UUJN No. 2 of 2014 related to obligations of a candidate notary and legal consequences that arise when there is a candidate notary who violate the provisions contained in Article 16A (2) UUJN No. 2 2014. The method used is a method normative research by using approach legislation. Based on the research results, it can be concluded that the ratio legis provisions of Article 16A (2) UUJN No. 2 of 2014 related to obligations of candidate notaries to keep all sesuatuu related to